Environmental factors in the etiology of type 1 diabetes, celiac disease, and narcolepsy. (July 2016) - Lernmark, Åke
Abstract : The etiology of human leukocyte antigen (HLA)‐associated organ‐specific autoimmune diseases is incomplete. In type 1 diabetes and celiac disease, the strongest associations are with the HLA‐DR3‐DQ2 and DR4‐DQ8 haplotypes, whereas the DQB1*06:02 allele has a strong negative association. In contrast, narcolepsy, especially as recently triggered by the Pandemrix ® H1N1 vaccine (GlaxoKlineSmith (GSK), Brentford, Middlesex, UK), did not seem to develop without at least one copy of the latter allele. The overall hypothesis is that the role of these different HLA haplotypes, especially in Finland and Sweden, is related to the immune response to infectious agents that are common in these two populations. The high incidence of both type 1 diabetes and celiac disease in Scandinavia may be the result of the HLA‐DR3‐DQ2 and DR4‐DQ8 haplotypes, and the DQB1*06:02 allele are common because they protected people from succumbing to common infections. The timing of dissecting the autoimmune response is critical to understand the possible role of environmental factors. First, an etiological trigger may be a common virus infecting beta cells or with antigens inducing beta‐cell cross reactivity. Second, an autoimmune reaction may ensue, perhaps in response to beta‐cell apoptosis or autophagy, resulting in autoantigen‐specific T cells and autoantibodies. It is critical in at‐risk children to dissect the immune response prior to the appearance of autoantibodies in order to identify cellular reactions in response to environmental factors that are able to induce an HLA‐associated immune reaction.